Early performance of eight broadleaved species grown as short rotation forest in England. (24th July 2021) - Mc Kay, H M; Harrison, A J; Connolly, T; Forster, J; Gregory, S; Smith, E; Clark, J
Abstract: The overall aim of the experiment was to compare the performance of a range of broadleaved species for their biomass production when grown for short rotations on ex-agricultural sites in England. The objectives were to compare over 7 years on four sites the survival, growth and biomass production of eight promising broadleaved species in relation to one another and two conifer species used as controls. Sites were planted in 2010/2011, and by winter 2016/2017 across all species and sites, the mean height, basal diameter (BD) and diameter at 1.3 m (DBH) were 444, 6.4 and 3.7 cm, respectively, despite considerable weed competition on these ex-agricultural sites. There were statistically significant main effects of species and site on all three measures and also significant interactions between sites and species. Totnes, the site with the highest mean annual temperature and the greatest rainfall, had the most uniform growth of the 10 species. At the three more variable sites, there was a general pattern of red alder ( Alnus rubra Bong.) with the greatest growth, followed by a group of Italian alder ( Alnus cordata (Loisel.) Duby), hybrid aspen ( Populus tremula L. x tremuloides Michx.) and common alder ( Alnus glutinosa (L.) Gaertner), then silver birch ( Betula pendula Roth) with moderate growth. Sycamore ( Acer pseudoplatanus L.), sweet chestnut ( Castanea sativa Miller) and ash ( Fraxinus excelsior L.), which had been infected with ash dieback, had the poorest growth. The estimated total stem volume after seven growing seasons averaged 31 m 3 ha −1, with red alder having the greatest volume production, followed by hybrid aspen and Italian alder. Calculated stem biomass (oven dry tonnes per hectare, odt ha −1 ) after seven growing seasons averaged over all sites and species was 14.1 odt ha −1 (equivalent to 7 tC). The rapid volume growth and intermediate wood density of red alder and Italian alder combined to give the greatest estimated biomass, averaging 34.5 (17 tC) and 24.0 odt ha −1 (12 tC). At three sites, the estimated biomass of red alder was around 40 odt ha −1 . Sitka spruce ( Picea sitchensis (Bongard) Carrière) and Japanese larch ( Larix kaempferi (Lamb.) Carrière) had a standing biomass estimated at 6.3 and 14.0 odt ha −1, respectively.